Factor Influences For Diagnosis And Vaccination Of Avian Infectious Bronchitis Virus (gammacoronavirus) In Chickens - Md. Safiul Alam Bhuiyan; Zarina Amin; Ag Muhammad Sagaf Abu Bakar; Suryani Saallah; Noor Hydayaty Md. Yusuf; Shafiquzzaman Siddiquee; Sharifudin Md Shaarani (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA